Generative artificial intelligence and its impact on marketing and sales - Landeo Julcarima , Victor Alfonso (2024)
The objective was to evaluate the impact of the implementation of generative artificial intelligence techniques on marketing and sales strategies. The research method was scientific, type and level of basic relational research, with a population of 100 companies from the Province of Huancayo and sample of 79. There is a significant relationship between generative artificial intelligence and the impact on marketing and sales with a correlational results (r=0.726,p<0.05), for the verification of specific hypothesis 1 the result was that the degree of significance between generative artificial intelligence and brand positioning was (r=0.531,p, 0.05) and finally the results of the to test the specific hypothesis 2 obtaining the result on whether there is a significant relationship between generative artificial intelligence and sales technologies was (r=0.358, p<0.05), in conclusion, there is a significant relationship between intelligence generative artificial and marketing and sales, generating competitive advantage in companies that use it unlike their competitors.